Navigating Contestation at the Corporate–Community Boundary: The Agonistic Work of Corporate Community Engagement Practitioners in Extractivist Projects - Hernández-Melgar, Eduardo (Journal of business ethics, 2026)
This paper contributes to the literature on Political Corporate Social Responsibility (PCSR) by offering a frontline perspective on the agonistic politics employed by Corporate Community Engagement (CCE) practitioners. While previous research has explored contestation by examining antagonisms at global levels, there has been a lack of focus on how such contestation is navigated at the individual and local level. This paper takes a micro, insider perspective to illuminate the antagonisms that CCE practitioners experience during engagement interventions. Drawing on a dataset of 50 interviews with CCE practitioners working in Global South spaces, the paper analyses qualitative data following the principles of Constructivist Grounded Theory. Our findings show that contestation materialises for CCE practitioners in temporal, rhythmical, and advocacy antagonisms. These antagonisms, while uncomfortable, are also invigorating, as practitioners draw on agonistic politics to interrogate power imbalances, legitimise the adversary, and accept unending struggles. By adopting an agonistic PCSR lens, this paper challenges a more traditional Habermasian PCSR approach that views deliberations as a teleological pathway to closure and rational consensus. Instead, our findings suggest that engagement and deliberation could be better conceptualised as an open-ended agonistic space where participants nurture their mutual understanding, not as enemies pursuing mutual rational superiority, but as adversaries uncovering each other’s critical interests and expectations.